Humic Acids Isolated from Selected Soils from the Russian Arctic and Antarctic: Characterization by Two-Dimensional 1H-13C HETCOR and 13C CP/Mas NMR Spectroscopy - Vyacheslav Polyakov; Evgeny V. Abakumov (Geosciences, 2019)
Here we describe the molecular composition and resistance to decomposition of humic acids isolated from selected soils of the Russian Arctic and Antarctic. The degree of soil organic matter stabilization was assessed using modern instrumental methods: nuclear magnetic resonance spectroscopy (cross peak magic-angle spinning (CP/MAS) 13C-NMR and 1H-13C heteronuclear-correlation (HETCOR)). Analysis of the humic acids showed that aromatic compounds prevail in the organic matter formed in cryoconites, located on the surfaces of the glaciers. The predominance of aliphatic fragments is revealed in the soils of the Yamal peninsula and Antarctica. This could be caused by sedimentation of fresh organic matter exhibiting low decomposition stage due to the severe climate and processes of hydrogenation in the humic acids, destruction of the C-C bonds, and formation of chains with high hydrogen content. These processes result in formation of aliphatic fragments in the humic acids.